Occupational health and safety problems among workers in the wood processing industries in Mutare, Zimbabwe - Jerie, Steven (Scholarlink Resource Centre, 2016)
The aim of this study was to assess the exposures and perceived risks (occupational, lifestyle and psychological factors) of workers in the wood processing industries in Mutare, Zimbabwe. This project is important in that it will reveal why health, safety and hygiene should be perceived as a priority in the wood processing industries of the Eastern Highlands of Zimbabwe. Usually industry owners and managers do not provide sufficient maintenance and funds to buy protective equipment. Not much attention is thus given to the safety of processing machines, equipment and tools as well as their link to health requirements in such enterprises. A detailed descriptive study was undertaken in the timber working industries of Mutare with a focus between August and October 2011. Random sampling was employed targeting the workers and management of the wood processing enterprises. The samples were drawn from the total employees in each of the two companies under survey. The first company with 1200 full-time workers and 800 contract workers had a sample size of 200 (10% of the total) and the second with 1400 workers had sample size of 140. The wood sector in Zimbabwe needs to be guided by a comprehensive national policy dealing with safety and health issues in the wood processing sector. Wood workers seem not to be covered by appropriate national safety and health standard. Managers are not taking keen account of the risks linked with wood processing. There is need to have precise knowledge on the subject and the various exposure levels need to be measured and monitored.